On flexible and green design. Perspectives and personal reflections - Lavinia Herzog; Thomas Herzog (Agathón)
The majority of humanity will live in megacities in the future. The world’s major cities recognise the connection between quality of life and green spaces. Green facades affect many parameters of a building, but human ‘biophilia’ is currently rarely a planning goal. While the effects of vegetation on the building climate can be of great importance, the potential sensory impact on the person inside needs to be taken into consideration as a subsystem in the buildings of the future. Architecture deals with the spirit of a place and with artefacts that relate to it. A characteristic of this is thinking in the different levels of the subsystems, cycles and time phases. Considering changes in the use and function of the built space while focusing on sustainable construction and renewable energies creates the chance of a performance-form of a performance-form of a specific architectural quality.